PERMASALAHAN PENDIDIKAN DI INDONESIA - ., Sukini (MAGISTRA, 2009)
This article is aimed at describing : (1) the Indonesian educations problems, (2) some factors causing the problems, and (3) the way out to solve those education problems through teaching and learning process. The methodology which is used in presenting this article is by observing directly to the factual teaching and learning process on the spot, and indirectly through literary observation. And then, the results are compared with the content of the law and legislation which regulate the education in Indonesia. The result show that there are many problems, including : (1) equal chances to get education, (2) the education quality and relevance, and (3) efficient and effective education. Those problems are emerged because of (1) the development of technology, (2) the population increase and (3) the implementation of teaching and learning process. Thats why, I try to the present some ways out through strategic steps that can be done by teachers/lecturers teach. There are three types of the way the students learn or study so that the teaching and learning process runs Impressively, i.e. learning somatically, auditorily and visually. Moreover, the way teachers teach must also be altered. Teacher (1) must not dominate the process, and (2) must act as a fascilitator and catalyst in it. Keyword: pendidikan, permasalahan pendidikan, pemerataan pendidikan, mutu pendidikan, relevansi pendidikan, efektivitas pendidikan, efisiensi pendidikan, dan pembelajaran